2018
DOI: 10.1016/j.mmcr.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of C. auris shunt infection with intraventricular caspofungin

Abstract: C. auris is an emerging fungal pathogen with high prevalence of resistance to current antifungal agents. Central nervous system infection with C. auris has been infrequently described. We describe here an adult with nosocomial CSF shunt infection due to multi drug resistant C. auris. Systemic therapy with echinocandin and flucytosine failed. Fortunately, administration of daily intraventricular caspofungin 10 mg for 10 days in conjunction with systemic voriconazole resulted in both clinical and microbiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…C. auris has been identified and reported as a cause of vulvovaginitis (from vaginal sample) and pericarditis (from last stage liver disease patient) and both these cases were reported from India . In another recent study from India, C. auris nosocomial cerebrospinal fluid shunt infection was reported in a 58‐year‐old patient . First donor‐derived C. auris infection in a lung transplant recipient was also reported in USA in 2017 .…”
Section: Identificationmentioning
confidence: 97%
“…C. auris has been identified and reported as a cause of vulvovaginitis (from vaginal sample) and pericarditis (from last stage liver disease patient) and both these cases were reported from India . In another recent study from India, C. auris nosocomial cerebrospinal fluid shunt infection was reported in a 58‐year‐old patient . First donor‐derived C. auris infection in a lung transplant recipient was also reported in USA in 2017 .…”
Section: Identificationmentioning
confidence: 97%
“…As synergistic interactions have a better efficacy, a combination therapy of an echinocandin and liposomal amphotericin B is prescribed in cases of unresponsiveness to echinocandins. [41][42][43] However, most recently in US, three cases of pan-resistant C. auris with resistance to all three classes of commonly prescribed antifungal drugs have been reported. 39 In the same report, it was mentioned that a total of 801 patients with C. auris were identified in New York as of June 28, 2019.…”
Section: Misidentification By Conventional Diagnostic Testsmentioning
confidence: 99%
“…25 Conversely, a systematic review of over 700 global cases from 2012 to 2017 demonstrated the majority of isolates were obtained from blood cultures, central line tip cultures or deep tissue samples, whilst urine isolates were less frequent. 12 Pericarditis, 26 central nervous system (CNS) shunt infection 27 and donor-derived infection after lung transplantation have also been described. 28 Colonisation of skin and mucosal surfaces often occurs in outbreaks.…”
Section: Clinical Syndromesmentioning
confidence: 99%